Impact of topical emollient, steroids alone or combined with calcipotriol, on the immune infiltrate and clinical outcome in psoriasis. Issue 11 (19th August 2022) - Heim, Marjorie; Irondelle, Marie; Duteil, Luc; Cardot‐Leccia, Nathalie; Rocchi, Stéphane; Passeron, Thierry; Tulic, Meri K.
Abstract: Psoriasis is a chronic inflammatory disease whereby long‐term disease control remains a challenge for the patients. Latest evidence suggests that combined topical treatment with steroids and vitamin D analogue foam (Calcipotriol/Betamethasone) is efficient in long‐term management of the disease and reducing the number of relapses. Its effects on cellular inflammation and cytokine production remain to be explored. We set out to examine the effect of topical therapies on cellular infiltrate and cytokine profile in the lesional skin of psoriasis patients. This was a monocentric, double‐blind, randomized trial with 30 patients. Patients were treated with the combined Calcipotriol/Betamethasone foam, Betamethasone foam alone, Clobetasol Propionate ointment or placebo. 4 mm skin biopsies from lesional and non‐lesional sites were taken before and 4 weeks after treatment. Cellular infiltrate, IFNγ and IL‐17 were studied by immunofluorescence. Each patient was their own control. Evolution in skin inflammation was studied in parallel with changes in patient's epidermal thickness and their tPASI clinical score. Lesional skin was characterized by increased epidermal thickness, increased number of IL‐17 and IFNγ producing CD8+ T cells, NK cells and neutrophils. All treatment reduced epidermal thickness and improved patients tPASI scores. Only the combined Calcipotriol/Betamethasone foam completely abolished epidermal and dermal influx of CD8+ T cells, reduced number of CD8 + IFNγ+ cells (but not CD8 + IL‐17+ cells) and significantly reduced the number of MPO+ neutrophils which were predominantly IL‐17+. None of the treatments had effect on NK cells. We have shown the combined topical treatment with Calcipotriol/Betamethasone foam to be effective in reducing cellular influx into lesional skin of psoriasis patients and this effect to be superior to emollient or Betamethasone alone. Its previously described efficacy in the clinic may be attributed to its unique and rapid ability to inhibit both adaptive CD8+ T cell and innate immune neutrophilia influx into the skin, which was not observed for the other treatments. Abstract : The text file should not be over 50 words long and should contain keywords that you feel people will use to search for your article. Topical Calcipotriol/Betamethasone foam is clinically effective in psoriasis. Here, we demonstrate a 4 weeks treatment to reduce cutaneous CD8+ T cells and neutrophils; later which was not achieved for other topical treatments (Betamethasone or Clobetasol Propionate). Reduced inflammation was associated with reduced epidermal thickness and tPASI score in the same patients.